Examining the Adoption of Prefabricated Construction Methods for Building Housing in Egypt - Nermeen Hatata; Maher El-nemr; Fatma Agrama (Journal of Engineering Research - Egypt, 2022)
Prefabricated construction methods have become a key strategy to achieve sustainable development in building housing around the world. However, these methods are still used in a narrow context in building Egyptian housing. This research aims to examine the adoption of prefabricated construction methods for building Egyptian housing. To achieve the aim of the research, 28 performance criteria under economic, social, environmental, and technical categories were used to evaluate the performance of prefabricated and traditional on-site frame construction methods in building Egyptian housing. Multi-criteria decision-making techniques (MCDM): the Technique for Order of Preference by Similarity to Ideal Solution technique (TOPSIS) and the Importance Performance analysis technique (IPA) were used to contextualize the final findings. The results revealed that prefabrication can achieve a good level of performance in building Egyptian housing with some recommendations. Most causes that weaken the performance of prefabrication in Egypt are back to the strategic criteria including; the lack of construction practitioners' knowledge, standardization availability, and customer perception. This research provides a notion about the prefabrication performance in building Egyptian housing by using the multi-criteria decision-making analysis.